Retinoblastoma tumor suppressor gene: An overview - Sunila Thomas; Anita Balan (Journal of Indian Academy of Oral Medicine and Radiology, 2012)
A genetic basis for the development of cancer has been hypothesized for nearly a century and has been supported by familial, epidemiological and cytogenetic studies. Current view is that carcinogenesis is a multistep process involving activation of oncogenes or inactivation of tumor suppressor genes. Tumor suppressor gene is a gene whose protein product can inhibit the transformation of a normal cell to a tumor cell and therefore, whose loss of function can contribute to the malignant transformation of cell. The retinoblastoma gene (Rb) is the first tumor suppressor gene identified and plays a key role in the regulation of cell cycle. A diverse body of evidence now indicates that pRb stands in the midst of a regulatory pathway and suffers disruption during the pathogenesis of majority of human tumors, including oral cancers- However, recent studies point to a more general function of pRb. In addition to tumor suppression, Rb has a role in cellular differentiation and apoptosis. This review provides an insight into the complex functions of pRb with particular reference to its role in tumor suppression.